Optimization on acrylic acid plant by using Aspen Plus - Yee Ket, Chiew (2013)
In this research of study, optimization of reactor and separators sections on acrylic acid production plant was investigated.In order to obtain higher production rate and maintain desired quality of products,the Aspen Plus simulator is used to simulate and optimize on the acrylic acid plant.The units proceed with optimization consists of reactor system,vapour recovery system(adsorption tower, and flash drum) and liquid recovery system(liquid-liquid extractor,and distillation column).The research methodology as separated into three phases,which are steady state simulation, sensitivity analysis and optimization. Based on the result obtained,the acrylic acid production plant was simulated successfully in Aspen Plus flow sheet and the final production rate of products is acceptable.For the optimization,optimum temperature of reactor is 315°C in order to obtain the maximum yield of acrylic acid which is 0.77254. For the flash drum unit,optimum temperature and pressure are 25°C and 4.84atm respectively.For the absorption tower and liquid-liquid extractor,optimum molar flow rate of water and solvent are 100kmol/h and 1350kmol/h respectively in order to recover more than 99% of acrylic and acetic acid.For the distillation column 1,optimum feed stages location,reflux ratio and re-boiler heat duty are number of 8, 4.44308 and 180000MJ/h respectively in order to maximize recovery of acids and solvent.For the distillation column 2,optimum feed stages location,reflux ratio and re-boiler heat duty are number of 23, 10.5 and 3000MJ/h respectively in order to maximize purity of acrylic acid. For overall result,it was found that by optimizing the operating conditions of units,desired quality of products is improved and more materials is recovered.